2017
DOI: 10.25115/ejrep.v7i17.1312
|View full text |Cite
|
Sign up to set email alerts
|

Percepciones y actitudes del alumnado extranjero y del profesorado: un estudio empírico en las aulas de acogida de Cataluña

Abstract: ResumenIntroducción. La investigación que presentamos intenta conocer las percepciones y las actitudes que el alumnado de origen extranjero que acude a las aulas de acogida de primaria de Cataluña y su profesorado tienen sobre la institución escolar, sobre su implicación en las prácticas escolares y sobre las relaciones que se allí se establecen.Método. Las percepciones fueron obtenidas mediante tres cuestionarios. Cada cuestionario consta de cuatro apartados: adaptación al medio escolar, estrategias de aprend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Numerous authors have revealed the importance of maintaining and recognizing the L1 when learning the L2 (Chireac et al, 2011;Navarro et al, 2016). Likewise, this is manifested through affective factors like self-esteem and self-confidence, as confirmed in studies carried out in Catalonia (Siqués et al, 2012;Vila et al, 2009) which concluded that those who feel the most valued and socially integrated developed more favourable attitudes towards the Catalan and Spanish languages, which in turn positively affects their language learning. Yet is the maintenance of home cultures actually facilitated at school?…”
Section: On the Adaptation Processmentioning
confidence: 96%
“…Numerous authors have revealed the importance of maintaining and recognizing the L1 when learning the L2 (Chireac et al, 2011;Navarro et al, 2016). Likewise, this is manifested through affective factors like self-esteem and self-confidence, as confirmed in studies carried out in Catalonia (Siqués et al, 2012;Vila et al, 2009) which concluded that those who feel the most valued and socially integrated developed more favourable attitudes towards the Catalan and Spanish languages, which in turn positively affects their language learning. Yet is the maintenance of home cultures actually facilitated at school?…”
Section: On the Adaptation Processmentioning
confidence: 96%
“…Furthermore, even though teachers may have access to establish close relations with immigrant families and get to know their sociocultural realities, some studies have shown that their perceptions of cultural diversity at schools tend to reflect general population attitudes to immigration on the larger society (Horenczyk & Tatar, 2002;Siqués et al, 2009;Vecina, 2006). Due to their position as members of the majoritarian society, teachers' social identities might be threatened by immigrants groups (Tajfel & Turner, 1979), triggering ambiguous or negative reactions towards them.…”
Section: Echelle D'attitude Envers Le Multiculturalisme à L'école: Vamentioning
confidence: 99%
“…Differences were further found between the various immigrant groups. Students coming from Latin America were often identified as the ones with the least favourable attitudes towards Catalan (Huguet, Janés & Chireac 2008;Lapresta et al 2009 This variation in language attitudes is most likely determined by the characteristics of each group, the specific experiences in the host society, their expectations, and social prejudices they might face (Siqués, Vila & Perera 2009;Lapresta, Huguet & Janés 2018;Alarcón, Parella & Yiu 2013;Alarcón & Garzón 2013). In this regard, the Japanese respondents were mainly temporary residents with plans to return to Japan or move to another country (Fukuda, 2016), while many of the other migrant groups had long-term plans to establish themselves in Catalonia (Alarcón, Parella & Yiu 2013).…”
Section: Language Attitudes and Immigration In Cataloniamentioning
confidence: 99%